Impact of seasonal changes on the vegetation composition of some selected areas in Lagos state, Nigeria - Adeonipekun, Peter Adegbenga; Oyebanji, Oyetola Olusegun; Adebayo, Michael Babatunde (Mediterranean Botany, 2019)
Rapid degradation of wetlands and habitat fragmentation are major threats to species diversity and ecological paradigm in Lagos state, Nigeria. Best to our knowledge, no empirical study has explored the effects of seasonal changes on covering three major cities in the statewithin the major cities in Lagos state. For this, we carried out a study covering the three major cities in Lagos: Badagry, Epe and Ikorodu. Permanent plots were randomly established for monthly data collection (quadrat method; size=10 x 10 m), that span across one-year period covering the wet and dry season). We observed two major vegetation types (secondary forest and mangrove) in the studied areas. Additionally, we documented 107 species belonging to 90 genera and 40 families. Species diversity analysis indicated higher diversity, abundance, species richness and evenness in Ikorodu and Epe during the wet has a greater while high species diversity was observed in Badagry during the dry season. The Dahomey gap phenomenon have greater implication on the Badagry vegetation while the coastal nature of Epe and Badagry negatively influenced their vegetation structure. Analyses inferred that species diversity pattern in the studied area seem to be determined by seasonal changes alongside anthropogenic activities and as a environmental factors (rainfall, geomorphology and geology). Further, our result suggests that Ikorodu could be regarded potential biodiversity hotspot area for conservation purposes because of its high floral composition and diversity. Therefore, improved management and conservation of the vegetation of the Ikorodu area is hereby recommended. The findings from this study will be useful in guiding the Physical Planning and Urban Development and Environment ministries in Lagos state for appropriate management and monitoring of developmental projects for sustainable development.